Comparative performance of spraying mechanisms under normal application range of speed and height of operations - Manickam, Ramesh Babu; Singh, Gajendra; Gupta, Chandra P.; Gee-Clough, D.; The Royal Norwegian Government (Bangkok : Asian Institute of Technology, 1987)
Four hand held sprayers namely Hand pressure sprayer operating on pressurization principle, Lever operated sprayer using continuous pressurization technique, Ultra low volume sprayer employing atomization technique, and Electro dynamic sprayer using electrical charging were tested using an experimental setup. Experiments were conducted to measure the variation in spray deposition efficiency and spray pattern over a width of 3 m in the walking speed range 0.8 to 2.0 kmph and application height 20 to 60 cm for given environmental conditions. Targets were selected and constructed based on the plant geometry, shape and leaf area of the paddy variety (RD-23). The percentage depositions of spray discharge on these targets were measured using a Photo spectrometer. The Electro dynamic sprayer was observed to give 1. 5 to 2 times better deposition than the sprayers operating on the principle of pressurisation. The spray pattern was observed to be more uniform in the case of Electro dynamic and Ultra low volume sprayers at 30 to 50 cm height, over a width 1.8 to 1.9 m. The distribution was observed to extend over a width 2.6 m in Lever operated sprayer whereas only very little traces were obtained in Hand pressure sprayer at 0.7 m from the nozzle central axis . In general, 30 to 50 cm height was observed to be the best range to obtain better deposition. The variation due to speed was significantly observed only in sprayers employing pressurization technique. The cost of operation was identified to be lesser in Ultra low volume and Electro dynamic sprayers as the area of usage increases.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1987
Keywords: Spraying equipment